Step–by–step plan for implementing a CRM system in a dental clinic - A. R. Grigoryan (Путеводитель предпринимателя, 2021)
During the crisis and the globalization of the economy, the CRM concept is considered the number one innovation in management. Initially, there were many negative reactions to CRM, but now it has become quite relevant and is gladly accepted by the heads of more than 75% of dental clinics. Thus, a private dental clinic was taken as a basis, as one of the leading and promising businesses in the Russian Federation.